The Role of Coenzymes on Mercury (Hg2+) Bioremediation by Isolates Pseudomonas aeruginosa KHY2 and Klebsiella pneumonia KHY3 - Neneng, Liswara; Gunawan, Yohanes Edy (Journal of Tropical Life Science, 2018)
Mercury pollution is dangerous to health. Previous research was found two potential Gram-negative bacteria for mercury bioremediation, from gold mining in Central Kalimantan, Indonesia. These isolates were identified as Pseudomonas aeruginosa KHY2 and Klebsiella pneumonia KHY3. Mechanisms of mercury bioremediation had not known yet by these isolates. This study purposed to test the role of coenzymes on mercury bioremediation by these isolate and to determine the coenzymes best level of mercury bioremediation. Experimental design was Completely Randomized Design in a laboratory. Treatment factors were coenzymes obtained from vitamins B1, B6, B12, with 6 levels of treatments, included 1 control. All treatments were done in Luria Broth media that contain 12 ppm of mercury. Mercury was measured by AAS Shimadzu AA-6200. The results showed that coenzymes effect was very significant to improve mercury bioremediation by P. aeruginosa KHY2 and K. pneumonia KHY3. Supplementation of vitamin B12 in culture media, more enhance of mercury bioremediation compared with vitamin B1 and B6. These result above, indicated the mechanism of mercury bioremediation in both isolates, were the enzymatic process.